Cuidadores(as) espirituais nos cuidados paliativos: revisão integrativa de literatura empírica - August, Hartmut (Horizonte, 2021)
Spiritual care is essential for the quality of services in palliative care (PC). This article presents a review of the empirical literature about spiritual caregivers working in palliative care. The method used was the integrative review, with a survey at CAPES Portal of Periodicals, PsycARTICLES and PubMed. After examining the 643 found publications, 54 studies were selected for analysis, and categorized into four major themes: "identity of spiritual caregivers", "training of spiritual caregivers", "practice of spiritual caregivers" and "practice impacts of spiritual caregivers". Spiritual care is crucial for the well-being and end-of-life quality, and transdisciplinary palliative care is fundamental in order to meet spiritual and psychosocial needs, which will be facilitated by the adoption of standardized methods. Training curricula and assessment tools allow a systematic assessment of the impact of education on patient, family and clinical staff. Considering the importance of religiosity in the Brazilian cultural context, the deepening of the spiritual care theme is of great relevance for professionals that work in palliative care. Bioethics and Theology are called upon to contribute with studies in this area so that spiritual care can be effectively integrated into PC teams.